Respuesta :
1.
When we divide two complex numbers, we multiply by the conjugate of the complex number in the denominator.
2. Remark: The conjugate of a+bi is a-bi.
[tex] \frac{3-2i}{1+4i}= \frac{(3-2i)}{(1+4i)} \frac{(1-4i)}{(1-4i)}= \frac{(3-2i)(1-4i)}{(1+4i)(1-4i)} [/tex]
[tex]\frac{(3-2i)(1-4i)}{(1+4i)(1-4i)}= \frac{3-4i-2i+(2i)(4i)}{1-(4i)^{2} } = \frac{3-6i-8}{1+16}= \frac{-5-6i}{17}= \frac{-5}{17}- \frac{6}{17}i [/tex]
When we divide two complex numbers, we multiply by the conjugate of the complex number in the denominator.
2. Remark: The conjugate of a+bi is a-bi.
[tex] \frac{3-2i}{1+4i}= \frac{(3-2i)}{(1+4i)} \frac{(1-4i)}{(1-4i)}= \frac{(3-2i)(1-4i)}{(1+4i)(1-4i)} [/tex]
[tex]\frac{(3-2i)(1-4i)}{(1+4i)(1-4i)}= \frac{3-4i-2i+(2i)(4i)}{1-(4i)^{2} } = \frac{3-6i-8}{1+16}= \frac{-5-6i}{17}= \frac{-5}{17}- \frac{6}{17}i [/tex]
Answer:
[tex]\frac{3-2i}{i+4}[/tex] is written in the form of a+bi as [tex]\frac{-11i}{17}+\frac{10}{17}[/tex]
Step-by-step explanation:
As given the expression in the question be
[tex]= \frac{3-2i}{i+4}[/tex]
Multiply denominator and numerator by i-4 .
[tex]= \frac{3-2i\times i-4}{i+4\times i-4}[/tex]
(As by using the property (a-b)(a+b)= (a² - b²))
Apply this in the above
[tex]= \frac{3-2i\times i-4}{i^{2} - 4^{2}}[/tex]
[tex]= \frac{3i-12-2i^{2}+8i}{i^{i}- 16}[/tex]
(As i² = -1 )
[tex]= \frac{11i-12-2\times -1}{-1 - 16}[/tex]
[tex]= \frac{11i-12+2}{-1 - 16}[/tex]
[tex]= \frac{11i-10}{-17}[/tex]
[tex]= \frac{-11i}{17}+\frac{10}{17}[/tex]
This is the representation of [tex]\frac{3-2i}{i+4}[/tex] is written in the form of a+bi .